2013
DOI: 10.5296/jse.v3i1.2969
|View full text |Cite
|
Sign up to set email alerts
|

The Use of Metacognitive Strategies in Listening Comprehension by Iranian University Students Majoring in English: a Comparison between High and Low Proficient Listeners

Abstract: This study aimed to investigate the types of metacognitive strategies used by Iranian university students majoring in English, and the differences in the use of these strategies between listeners across two levels of high and low proficiency. The results revealed that Iranian university students used "problem-solving strategies" most frequently and "person-knowledge strategies" least frequently. It was also found that more proficient listeners used metacognitive strategies more frequently than less proficient … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
17
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(25 citation statements)
references
References 34 publications
8
17
0
Order By: Relevance
“…Meanwhile, the highest level of their listening strategy awareness related to problem-solving refers to kinesthetic learners. The present findings are in line with the other studies that English department students were found to be more aware of their problem solving and planning and evaluation strategies (Rahimi and Katal, 2012;Ratebi and Amirian, 2013).…”
Section: Planning and Evaluation And Problem Solvingsupporting
confidence: 93%
See 1 more Smart Citation
“…Meanwhile, the highest level of their listening strategy awareness related to problem-solving refers to kinesthetic learners. The present findings are in line with the other studies that English department students were found to be more aware of their problem solving and planning and evaluation strategies (Rahimi and Katal, 2012;Ratebi and Amirian, 2013).…”
Section: Planning and Evaluation And Problem Solvingsupporting
confidence: 93%
“…Altuwairesh' (2016) research findings are in line with the present study that EFL learners in King Saud University report the use of problem-solving strategies is more than the other types of metacognitive listening strategies. The study conducted by (Ratebi & Amirian, 2013)also supported the present study finding that metacognitive awareness for problem-solving had the highest score for EFL learners in Iranian University. Thus, listening strategies associated with the explicit instruction of the strategies including making an inference, listening tokeywords, and recognizing unfamiliar words.…”
Section: Planning and Evaluation And Problem Solvingsupporting
confidence: 86%
“…On the other hand, no significant differences were found between other types. This result agrees with the other studies reviewed in the literature which found that problem-solving strategies are used more frequently than other types of metacognitive listening strategies (Chamot & Küpper, 1989;Graham, 2003;Vandergrift et al, 2006;Ratebi, 2013;Altuwairesh, 2016). This result indicates that Saudi EFL medical students resort to their repertoire of vocabulary and the general idea of the text to deduce the meaning of elt.ccsenet.org English Language Teaching Vol.…”
Section: Statementsupporting
confidence: 82%
“…The study also indicated that giving up listening when having a problem is not favoured by students (Vogely, 1995). This result also was reported by other researchers (Li, 2013;Ratebi, 2013;Altuwairesh, 2016).…”
Section: Statementsupporting
confidence: 76%
See 1 more Smart Citation